Analisis Keterpaduan Kurikulum dan Buku Teks Ekonomi SMA dalam Implementasi Kurikulum Berbasis Kompetensi (KBK) 2004 - Jelita Angeli Purba; Agnes Anggreni Tamba; Krisentia Angelina Napitu; Pintar Rohsangapta Padang; Ade Asminariah Sihombing (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to analyze the extent of consistency between the 2004 Competency-Based Curriculum (KBK) and the high school Economics textbooks used as primary learning resources. Using a qualitative method and document analysis, this research evaluates the alignment of the Standard Competencies, Basic Competencies, instructional materials, and learning approaches presented in the textbooks with the competency requirements outlined in the KBK. The findings reveal significant inconsistencies, as the textbooks still place excessive emphasis on theoretical content and cognitive exercises, whereas the KBK expects the development of analytical competencies, attitudes, and skills through contextual learning. In addition, the textbooks do not sufficiently acknowledge the importance of social values, economic ethics, or relevant local case studies that reflect students’ real-life contexts. These discrepancies lead to learning practices that remain teacher-centered, failing to fully support the constructivist principles underlying the KBK. This study recommends strengthening the alignment between the curriculum and textbooks by incorporating local contexts, providing practical and authentic examples, implementing project-based activities, and designing assessments that equally cover cognitive, affective, and psychomotor aspects to optimally achieve the goals of the KBK.